2007
DOI: 10.1016/j.scitotenv.2007.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic intake via water and food by a population living in an arsenic-affected area of Bangladesh

Abstract: 13 14More and more people in Bangladesh have recently become aware of the risk of drinking 15 arsenic-contaminated groundwater, and have been trying to obtain drinking water from less 16 arsenic-contaminated sources. In this study, arsenic intakes of 18 families living in one block of a rural 17 village in an arsenic-affected district of Bangladesh were evaluated to investigate their actual arsenic 18 intake via food, including from cooking water, and to estimate the contribution of each food category 19 and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
98
2
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(106 citation statements)
references
References 20 publications
5
98
2
1
Order By: Relevance
“…A previous study in children older than 10 years old reported that the daily water intake via direct drinking on an average day was 2.7 L/day (1.7-3.3 L/day) and 2 L/day (1.2-2.7 L/ day) for male and female children, respectively [15]. Moreover, according to some previous studies, the contribution of raw food to As exposure based on daily intake is minor compared with the amount from drinking water.…”
Section: Discussionmentioning
confidence: 95%
“…A previous study in children older than 10 years old reported that the daily water intake via direct drinking on an average day was 2.7 L/day (1.7-3.3 L/day) and 2 L/day (1.2-2.7 L/ day) for male and female children, respectively [15]. Moreover, according to some previous studies, the contribution of raw food to As exposure based on daily intake is minor compared with the amount from drinking water.…”
Section: Discussionmentioning
confidence: 95%
“…The grain samples were dehusked, powderized, and 0.2 g weighed into a 50 mL polyethylene centrifuge tube. Samples were extracted with 1% HNO 3 …”
Section: Methodsmentioning
confidence: 99%
“…Arsenic exposure through food poses a substantial risk to humans in certain parts of the world, particularly in Asia from the consumption of staple foods such as rice and vegetables, which have been irrigated with As-rich groundwater (Meharg et al 2009;Mondal and Polya 2008;Kile et al 2007;Smith et al 2006). However, drinking water is seen to pose the most significant risk to human health in Argentina, primarily through consumption and cooking, this is due to the various potential sources of arsenic present in the region, such as in groundwater and surface water (Nguyen et al 2009;Asante et al 2007;Ning et al 2007;Ohno et al 2007). …”
Section: Introductionmentioning
confidence: 99%